A New Double Doped Bismuth Oxide with Stable Ionic Conductivity at Intermediate Temperatures. (30th May 2017) - Jolley, Adam G.; Wachsman, Eric D.
Abstract : While the FCC cubic phase of doped Bi2 O3 exhibits very high oxygen ion mobility at elevated temperatures, the conductivity ultimately suffers at intermediate temperatures due to the oxygen sublattice ordering. Traditional bismuth oxide based electrolytes are not suitable in solid oxide fuel cells that operate below approximately 600°C due to the ordering phenomenon. Reported herein is a Bi2 O3 electrolyte material that does not order below 600°C. In the 550°C- 500°C temperature range the electrolyte material does not exhibit noticeable degradation of conductivity, even after annealing for one hundred hours. The oxygen ion conductivity of the material is comparable to notable FCC cubic Bi2 O3, and has superior conductivity to other prominent SOFC electrolytes such as GDC, SNDC, and YSZ. This double doped bismuth based electrolyte would allow for a high performing and stable SOFC operating at intermediate temperatures.